Extraction of inflation expectations from financial instruments - Alberto Fuertes; Ricardo Gimeno; José Manuel Marqués (Inter-American Development Bank (IDB), 2018)
In this paper we estimate inflation expectations for several Latin American countries using an affine model that takes as factors the observed inflation and the parameters generated from zero-coupon yield curves of nominal bonds. By implementing this approach, we avoid the use of inflation-linked securities, which are scarce in many of these markets, and obtain market measures of inflation expectations free of any risk premium, eliminating potential biases included in other measures such as breakeven rates. Our method provides several advantages, as we can compute inflation expectations at any horizon and forward rates such as the expected inflation over the five year period that begins five years from today. We find that inflation expectations in the long-run are fairly anchored in Chile and Mexico, while those in Brazil and Colombia are more volatile and less anchored. We also find that expected inflation increases at longer horizons in Brazil and Chile, while it is decreasing in Colombia and Mexico.
Keywords: G12; E43; E44; C54; 330; Inflation expectations; Affine model; Real interest rate; Risk premium